The Iraqi Dialect in Quranic Recitations (Journal of the College of Basic Education, 2025)
This study investigates Quranic terms preserved in the Iraqi dialect, highlighting their phonetic and semantic connections with Classical Arabic. The research is divided on two main sections: the first explores the phenomenon of hamza facilitation in Quranic recitations and its reflection in Iraqi speech, while the second examines terms that retained their original structure but occasionally underwent semantic shifts, such as ʾī (yes) and shaqāwa (mischief). A descriptive-analytical approach was adopted to trace the interplay between the phonetic system of the Iraqi dialect and the phonological features of Quranic vocabulary. The findings reveal that the presence of Quranic expressions in Iraqi everyday language underscores the enduring influence of the Qur’an on the phonetic and lexical dimensions of Arabic dialects. Moreover, phonetic features such as tashīl al-hamza remain distinctive markers of linguistic interaction between Classical Arabic and vernacular usage. This study emphasizes the role of Quranic readings in preserving Arabic dialectal features and documenting their semantic development